Polishing composition and method for chemical mechanical polishing of substrate

By using the first polymer coated alumina abrasive particles and the second polymer weakly adsorbed on the surface of the coating in copper chemical mechanical polishing, the stability problem of Al2O3 abrasive particles in the full pH range is solved, and stable dispersion within the pH range of 8-10 is achieved and storage time is extended, while ensuring good grinding performance.

CN119842365APending Publication Date: 2025-04-18WUHAN DINGZE NEW MATERIAL TECH CO LTD +3
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411830147.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

In copper chemical mechanical grinding, Al2O3 abrasive particles have poor stability in an acidic environment, resulting in instability of the polishing composition under the full pH range, which in turn affects the polishing effect and the storage time of the composition.

Method used

By adding the first polymer and the second polymer, the first polymer covers the surface of the alumina abrasive particles, making them negatively charged and improving stability; the second polymer weakly adsorbs the surface of the cladding layer of the alumina abrasive particles to prevent agglomeration of the abrasive particles and prolongs the storage time of the composition.

Benefits of technology

In the grinding composition with a pH value of 8-10, the alumina abrasive particles remain dispersed and stable, extending the storage time of the composition, while ensuring good grinding performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005185359280000071
    Figure BDA0005185359280000071
  • Figure BDA0005185359280000072
    Figure BDA0005185359280000072
  • Figure BDA0005185359280000081
    Figure BDA0005185359280000081
Patent Text Reader

Abstract

The invention provides a composition for grinding and a method for carrying out chemical mechanical grinding on a base material, and relates to the technical field of chemical reagents for semiconductor manufacturing. The composition for grinding comprises aluminum oxide abrasive particles with the average primary particle size of 80-140 nm, a first polymer, a second polymer and a pH regulator, the first polymer is a negatively charged polymer or copolymer, and the pH value of the composition for grinding is 8-10. By adding the first polymer and the second polymer, the first polymer coats the surfaces of the aluminum oxide abrasive particles to improve the stability of the composition for grinding, and the second polymer generates weak adsorption on the surfaces of coating layers of the aluminum oxide abrasive particles to prevent agglomeration of various abrasive particles and further stabilize the system. Under the combined action of the first polymer and the second polymer, the aluminum oxide abrasive particles can be stably dispersed in the grinding composition with the pH value of 8-10, and the storage time of the grinding composition can be prolonged under the condition of ensuring that the grinding composition has better grinding performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of chemical reagents for semiconductor manufacturing, and in particular to a polishing composition and a method for chemical mechanical polishing of a substrate. Background Art

[0002] Chemical mechanical polishing (CMP) is currently the only practical technology and core technology that can achieve global planarization of wafers. With the development of very large-scale integrated circuits, the feature size has decreased and the number of layers has increased. Copper wiring has successfully replaced aluminum wiring in this field. As a key processing technology for copper workpieces, CMP has also developed rapidly in the application of copper grinding. Since copper has a high grinding rate in acidic solutions, early grinding compositions for copper grinding were mainly acidic. However, acidic grinding compositions often cause uncontrollable defects on the wafer surface due to their corrosive effect on copper. Therefore, the development of neutral and alkaline grinding compositions is the main research direction at present.

[0003] In copper CMP, the mechanical effect brought by the high hardness of Al2O3 abrasive can be relied on to quickly grind the copper surface. The zeta potential of Al2O3 abrasive is positive and is only stable in an acidic environment. The isoelectric point is generally around 8-9, while the pH of Cu CMP slurry is generally above 7 (because copper corrodes too quickly in acidic conditions to be controlled). At this time, the stability of Al2O3 abrasive is very poor. Anionic polymers are usually coated on the surface of Al2O3 abrasives to make the zeta potential of the abrasives negative at all pH values, thereby improving stability. However, anionic polymers may dissociate in systems with high small molecule content, resulting in the problem of abrasive reagglomeration and sedimentation. Summary of the invention

[0004] The present application provides a polishing composition and a method for chemical mechanical polishing of a substrate. By adding a first polymer and a second polymer, the first polymer can be coated on the surface of at least part of the aluminum oxide abrasive particles, so that the surface of the aluminum oxide abrasive particles is negatively charged, thereby improving the stability of the polishing composition under electrostatic interaction; the second polymer can be weakly adsorbed on the surface of the coating layer of the aluminum oxide abrasive particles to prevent the agglomeration of multiple abrasive particles, thereby further playing a role in stabilizing the system.

[0005] In a first aspect, the present application provides a polishing composition comprising:

[0006] Alumina abrasive particles with an average primary particle size of 80-140 nm, a first polymer, a second polymer, a grinding accelerator, and a pH adjuster, wherein the first polymer and the second polymer will ionize hydrogen ions and negatively charged groups in an aqueous solution, the molecular weight of the second polymer is in the range of 2000-100000 g / mol, and the pH value of the grinding composition is 8-10;

[0007] The polishing composition comprises the following preparation method:

[0008] S1: adding the first polymer to water, then adjusting the pH to 4-6 with the pH adjuster, adding the dispersion of the aluminum oxide abrasive under high-speed shearing, and dispersing for 2 hours;

[0009] S2: adding the grinding accelerator and adjusting the pH to 8-10 with the pH regulator;

[0010] Wherein, the second polymer is added in the step S1.

[0011] In a possible implementation manner, the second polymer has a carboxyl group and / or a phosphate group.

[0012] In a possible implementation, the second polymer is selected from one or more of polyacrylic acid, hypophosphite-based polyacrylic acid, and polystyrene sulfonic acid.

[0013] In a possible implementation, the molecular weight of the second polymer is greater than the molecular weight of the first polymer.

[0014] In a possible implementation, the second polymer is added after the dispersion of the aluminum oxide abrasive particles.

[0015] In a possible implementation, the molecular weight of the first polymer is in the range of 2000-40000 g / mol.

[0016] In a possible implementation, the first polymer is a sulfonic acid-based polymer, and the first polymer is selected from one or more of poly(2-acrylamido-2-methyl-1-propanesulfonic acid), poly(3-acrylamido-1-propanesulfonic acid), and polyacrylamide-polypropylenesulfonic acid copolymer.

[0017] In a possible implementation, the content of the first polymer is in the range of 0.1-1.2 wt %, and the content of the second polymer is in the range of 0.02-0.2 wt %.

[0018] In a possible implementation, the grinding accelerator is a small molecule acid selected from one or more of glycine, citric acid, malonic acid, and tartaric acid.

[0019] In a second aspect, the present application provides a method for chemical mechanical polishing of a substrate, comprising:

[0020] (i) contacting a substrate with a polishing pad and the polishing composition according to any one of the embodiments of the first aspect,

[0021] (ii) moving the polishing pad relative to the substrate with the polishing composition between the polishing pad and the substrate, and

[0022] (iii) grinding away at least a portion of the substrate to abrade the substrate.

[0023] In the above technical solution, by adding the first polymer and the second polymer, the first polymer can be coated on the surface of at least part of the aluminum oxide abrasive particles, so that the surface of the aluminum oxide abrasive particles is negatively charged, and the stability of the grinding composition is improved under electrostatic interaction; the second polymer can be weakly adsorbed on the surface of the coating layer of the aluminum oxide abrasive particles to prevent the agglomeration of various abrasive particles, and further play a role in stabilizing the system. Under the joint action of the first polymer and the second polymer, the aluminum oxide abrasive particles can maintain a stable dispersion in the grinding composition with a pH value between 8 and 10, which is conducive to extending the shelf life of the grinding composition while ensuring that the grinding composition has good grinding performance. DETAILED DESCRIPTION

[0024] In order to make the purpose, technical scheme and advantages of the embodiments of the present application clearer, the technical scheme in the embodiments of the present application will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to the conventional conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0025] It should be understood that the term “and / or” used in the specification and appended claims of this application refers to any and all possible combinations of one or more of the associated listed items, and includes these combinations.

[0026] In addition, in the description of the present application specification and the appended claims, the terms "first", "second", "third", etc. are only used to distinguish the descriptions and cannot be understood as indicating or implying relative importance.

[0027] It should be noted that the following embodiments are examples of the present application and are only used to illustrate the present application, but not to limit the present application. Other combinations and various improvements within the concept of the present application may be made without departing from the subject matter or scope of the present application.

[0028] The polishing composition and the method for chemical mechanical polishing of a substrate provided in the present application are described in detail below.

[0029] The polishing composition of the embodiment of the present application comprises: aluminum oxide abrasive particles with an average primary particle size of 80-140 nm, a first polymer, a second polymer, a polishing accelerator, and a pH adjuster. The first polymer and the second polymer will ionize hydrogen ions and negatively charged groups in an aqueous solution. The molecular weight of the second polymer is in the range of 2000-100000 g / mol. The pH value of the polishing composition is 8-10. The preparation method of the polishing composition is as follows:

[0030] S1: adding the first polymer to water, then adjusting the pH to 4-6 with a pH adjuster, adding the dispersion of aluminum oxide abrasive particles under high-speed shearing, and dispersing for 2 hours;

[0031] S2: Add grinding accelerator and adjust pH to 8-10 with pH regulator;

[0032] The second polymer is added in step S1. That is, the second polymer can be added to water together with the first polymer; it can also be added to water together with the dispersion of aluminum oxide abrasive grains after the first polymer; or it can be added after the dispersion of aluminum oxide abrasive grains is added to water.

[0033] The smaller the particle size of the aluminum oxide abrasive, the better the dispersibility of the abrasive, and the stronger the stability of the aluminum oxide abrasive in the liquid. However, the smaller the particle size, the slower the polishing speed of the aluminum oxide. From the perspective of polishing materials at a higher polishing speed, the average primary particle size of the aluminum oxide abrasive can be 80 nm or more. The larger the particle size of the aluminum oxide, the more obvious the gravity sedimentation effect is, which will affect the stability. From the perspective of improving the stability of the polishing composition and extending the abrasive agglomeration sedimentation time, the average primary particle size of the aluminum oxide abrasive can be 140 nm or less.

[0034] The first polymer can dissociate into negatively charged groups, and the first polymer and the aluminum oxide abrasive particles undergo electrostatic interaction, and the first polymer can be coated on at least part of the surface of the aluminum oxide abrasive particles. Under the electrostatic interaction, the steric exclusion effect between the aluminum oxide abrasive particles is strong, which improves the dispersion performance of the aluminum oxide abrasive particles and reduces the sedimentation rate of aluminum oxide, thereby facilitating the improvement of the stability of the polishing composition.

[0035] The second polymer can dissociate negatively charged groups. The second polymer is used to weakly adsorb on the surface of the coating layer of the first polymer-coated aluminum oxide abrasive, avoiding the failure of the polymer coating caused by the replacement of the first polymer by other small molecule compounds, thereby avoiding the reduction of the spatial exclusion effect between the aluminum oxide abrasives and rapid agglomeration, preventing the agglomeration of various abrasives, and thus playing a role in stabilizing the system. The molecular weight of the second polymer ranges from 2000 to 100000 g / mol. Since the second polymer will be weakly adsorbed on the surface of the coating layer of the aluminum oxide abrasive, when the molecular weight of the second polymer is too large, it will also cause the coating layer on the surface of the aluminum oxide abrasive to be too thick, making the particle size of the coated aluminum oxide abrasive too large, and being affected by gravity sedimentation, affecting stability, resulting in a short agglomeration sedimentation time of the abrasive, and the grinding composition cannot be stored for a long time.

[0036] The pH adjuster can be an organic base or an inorganic base, or an organic acid or an inorganic acid. For example, acid components such as acetic acid, nitric acid, sulfuric acid, hydrochloric acid, phosphoric acid, and boric acid; and alkaline components such as ammonia water, potassium hydroxide, sodium hydroxide, calcium hydroxide, sodium methoxide, sodium ethoxide, triethylamine, and triethanolamine can be cited. The pH adjuster adjusts the pH value of the polishing composition to between 8 and 10 to prevent copper from corroding too quickly and uncontrollably in an acidic environment.

[0037] The grinding composition provided by the present application is provided with a first polymer and a second polymer. The first polymer can be coated on the surface of at least part of the aluminum oxide abrasive particles, so that the surface of the aluminum oxide abrasive particles is negatively charged, and the stability of the grinding composition is improved under electrostatic interaction; the second polymer can be weakly adsorbed on the surface of the coating layer of the aluminum oxide abrasive particles to prevent the agglomeration of various abrasive particles, and further play a role in stabilizing the system. Under the joint action of the first polymer and the second polymer, the aluminum oxide abrasive particles can maintain dispersion and stability in the grinding composition with a pH value between 8 and 10, which is conducive to extending the shelf life of the grinding composition while ensuring that the grinding composition has good grinding performance.

[0038] In the present application, the grinding accelerator is a small molecule acid, which can be selected from one or more of gluconic acid, lactic acid, citric acid, tartaric acid, malic acid, glycolic acid, malonic acid, formic acid, oxalic acid, acetic acid, propionic acid, peracetic acid, succinic acid, lactic acid, aminoacetic acid, phenoxyacetic acid, diglycolic acid, glutamine, aspartic acid, glycine, glutamic acid, arginine, and lysine. Preferably, the small molecule acid is selected from one or more of glycine, citric acid, malonic acid, and tartaric acid. The small molecule acid can be used as a grinding accelerator to increase the grinding speed of the grinding composition, and can also be used as a pH regulator to adjust the pH value of the grinding composition. When a grinding accelerator is used, it is usually present in the grinding composition at a concentration in the range of about 0.01wt% to about 5wt%, for example, about 0.05wt% to about 3wt% when used.

[0039] In the present application, the first polymer is a sulfonic acid-based polymer, examples of which include: poly(acrylic acid-sulfonic acid), poly(acrylic acid-2-acrylamido-2-methylpropane sulfonic acid (AMPS)), poly(2-acrylamido-2-methyl-1-propane sulfonic acid), poly(acrylic acid-AMPS-styrene sulfonic acid), poly(acrylic acid-allylbenzene sulfonate), poly(3-acrylamido-1-propane sulfonic acid), poly(acrylic acid-2-acrylamido-tert-butyl sulfonic acid), polyacrylamide-polypropylene sulfonic acid copolymer, and the like.

[0040] Preferably, the first polymer also has a positive potential point containing N, such as an amino group, an aminopropyl group, an aminoethyl group, etc. Such a site is conducive to further weak adsorption of the second polymer on the surface of its coating layer, blocking other small molecular compounds from binding to the surface of the aluminum oxide abrasive, thereby playing a role in stabilizing the system. Preferably, the first polymer is selected from one or more of poly(2-acrylamido-2-methyl-1-propanesulfonic acid), poly(3-acrylamido-1-propanesulfonic acid), and polyacrylamide-polypropylene sulfonic acid copolymer.

[0041] In the present application, the molecular weight of the first polymer is in the range of 2000-40000 g / mol. If the molecular weight of the first polymer is too high, the hydration layer of the aluminum oxide abrasive grains will be too thick, and such aluminum oxide abrasive grains will also be unstable and cause sedimentation.

[0042] In the present application, the first polymer is measured by weight, and preferably the content of the first polymer is in the range of 0.1-1.2 wt %.

[0043] In the present application, the second polymer has a carboxyl group and / or a phosphate group. Among them, examples of carboxyl polymers include polyacrylic acid, polymethacrylic acid, sodium polyacrylate, polyacrylamide and sodium polymethacrylate, poly-p-methoxystyrene, polystyrene sulfonic acid, polymaleic acid, polyfumaric acid, polyitaconic acid, poly(p-styrene carboxylic acid), polyacrylamide, polyamic acid, polyglyoxylic acid, polystyrene carboxylic acid, etc. Examples of phosphate polymers include potassium polyphosphate, ammonium polyphosphate, calcium polyphosphate, phosphinyl polyacrylic acid, polyacrylic acid / phosphoric acid copolymer, polyphosphoric acid / acrylamide copolymer, etc. Preferably, the second polymer is selected from one or more of polyacrylic acid, phosphinyl polyacrylic acid, and polystyrene sulfonic acid.

[0044] In the present application, the molecular weight of the second polymer is greater than that of the first polymer. When the molecular weight of the second polymer is too small, the second polymer will replace the first polymer and be adsorbed on the surface of the aluminum oxide abrasive to form a coating layer. However, if the first polymer is not adsorbed on the surface of the aluminum oxide abrasive, the copper removal rate will be low and the polishing effect of the polishing composition will be poor. Therefore, the molecular weight of the second polymer is greater than that of the first polymer.

[0045] In the present application, preferably, the second polymer is added after the aluminum oxide abrasive. If the first polymer and the second polymer are in contact with the aluminum oxide abrasive at the same time, the coating structure of the aluminum oxide abrasive is unstable, and the aluminum oxide abrasive will still agglomerate, resulting in a short shelf life. If the first polymer contacts the aluminum oxide abrasive first and then the second polymer is added, the aluminum oxide abrasive will not agglomerate and can be stored for a longer time. Such a feeding order can effectively improve the stability of the aluminum oxide abrasive and prevent other small molecule compounds from replacing the surface coating sites of the aluminum oxide abrasive, thereby enabling the grinding composition to be stored for a long time.

[0046] In the present application, the second polymer is measured by weight, and preferably the content of the second polymer is in the range of 0.02-0.2 wt %.

[0047] In a second aspect, the present application further provides a method for chemical mechanical polishing of a substrate, comprising: (i) contacting the substrate with a polishing pad and a polishing composition according to any one of claims 1 to 9, (ii) moving the polishing pad relative to the substrate, with the polishing composition between the polishing pad and the substrate, and (iii) grinding away at least a portion of the substrate to polish the substrate.

[0048] Although the polishing composition of the present application can be used to polish any substrate (e.g., integrated circuits, metals, ILD layers, semiconductors, and thin films), the polishing composition can be particularly used to polish a substrate comprising at least one copper or copper-containing alloy, and can further comprise any suitable insulating, metal, or alloy layer (e.g., a metal conductive layer), the insulating layer can be a metal oxide, a porous metal oxide, glass, an organic polymer, a fluorinated organic polymer, or any other suitable high or low K value insulating layer, the insulating layer is preferably a silicon-based metal oxide, and the substrate preferably further comprises a metal layer comprising tantalum, tungsten, or titanium.

[0049] The technical solution of the present invention is further described below in conjunction with specific embodiments.

[0050] The grinding compositions in the following examples and comparative examples were prepared using the following method:

[0051] S1: Add 0.8% of the first polymer to water, then adjust the pH to 4-6 with aqueous ammonia, add 10% alumina abrasive dispersion (DLA series alumina, Hubei Dinglong New Materials) at a rate of 25 mL / min under high shear, and disperse for 2 hours;

[0052] S2: Add a grinding accelerator (tartaric acid or citric acid) and adjust the pH of the solution to 8-10 with aqueous ammonia.

[0053] In the following embodiments and comparative examples, "first add A and then add B" means adding the second polymer after adding the aluminum oxide abrasive dispersion; "A and B are added together" means adding the second polymer and the first polymer together into water, or, after the first polymer, the second polymer and the aluminum oxide abrasive dispersion are added into water together.

[0054] The first polymer is poly(3-acrylamido-1-propanesulfonic acid), the second polymer is phosphite-based polyacrylic acid, and the addition ratio of the second polymer is 0.1%.

[0055] In the Examples and Comparative Examples, the physical properties and evaluation methods of the aluminum oxide abrasive grains and the polishing composition were measured according to the following methods:

[0056] (1) The particle size of aluminum oxide abrasive was measured using a MOD DC24000 UHR particle size analyzer;

[0057] (2) The particle size of the alumina abrasive after coating was measured using a Malvern Zetasizer PRO;

[0058] (3) Sedimentation time: Place the prepared polishing composition in a 100 mL beaker to the highest scale line, seal it with a sealing film, and leave it at room temperature. The time it takes for the upper solution to settle to the 50 mL scale line and become clear and transparent is defined as its sedimentation time. If the sedimentation time of the polishing composition is less than 100 days, there is no need to measure its polishing rate.

[0059] (4) Specific grinding conditions: the test machine is Reflexion LK; the flow rate of the grinding composition is 200 mL / min; the grinding pad is DH3210 (produced by Hubei Dinghui Microelectronics Materials Co., Ltd.); the dressing disc is DK4703 (produced by Wuhan Huida Materials Technology Co., Ltd.); the pressure is 3.0 psi; the rotation speed of the grinding disc and the grinding head is 93 / 87 rpm; the grinding time is 1 min;

[0060] (5) Copper removal rate: The difference in copper film thickness before and after grinding for 1 min is the copper removal rate. The film thickness is measured using a four-probe resistivity tester.

[0061] Table 1 Components and evaluation results of the polishing compositions of Examples 1-3 and Comparative Examples 1-2

[0062]

[0063] By comparing Examples 1-3 and Comparative Examples 1-2, it can be found that when the alumina particle size increases, the alumina with a larger particle size is more significantly affected by gravity sedimentation, the system is more unstable, and the alumina sedimentation is faster. When the alumina particle size is too large, the alumina is significantly affected by gravity sedimentation, the stability is low, and the grinding composition cannot be stored for a long time; when the alumina particle size is too small, the grinding rate of the grinding composition is low.

[0064] Table 2 Components and evaluation results of the polishing compositions of Examples 1-3 and Comparative Examples 3-5

[0065]

[0066] By comparing Examples 1-3 and Comparative Examples 3-5, it can be found that when the second polymer B is not added, the addition of the grinding accelerator will greatly reduce the stability of the system, resulting in rapid sedimentation of aluminum oxide. When the second polymer B is added, the aluminum oxide system can be stabilized, the sedimentation rate of aluminum oxide abrasive particles can be greatly slowed down, and the grinding composition can be stored for a long time.

[0067] Table 3 Components and evaluation results of the polishing compositions of Examples 2, 4-5 and Comparative Examples 4, 6-8

[0068]

[0069] Through Examples 2, 5 and Comparative Examples 4, 6, it can be found that when the molecular weight of the first polymer A increases, the addition of a grinding accelerator and a second polymer B, compared with the addition of a grinding accelerator without adding the second polymer B, the difference in sedimentation time of the grinding composition is greater, that is, the phenomenon of rapid sedimentation of aluminum oxide is more obvious, indicating that the first polymer A with a larger molecular weight is more easily replaced by the grinding accelerator in its adsorption site, resulting in a decrease in the stability of aluminum oxide.

[0070] Furthermore, by comparing Examples 2, 4-5 and Comparative Examples 7-8, it can be found that when the molecular weight of the first polymer A is small, the dispersion performance of aluminum oxide is similar, but when the molecular weight of the first polymer A is too large, the sedimentation time of the aluminum oxide abrasive is greatly shortened and the stability is reduced.

[0071] Table 4 Components and evaluation results of the polishing compositions of Examples 2, 6-9 and Comparative Examples 9-11

[0072]

[0073] By comparing Examples 2, 6-9 and Comparative Example 9, it can be found that as the molecular weight of the second polymer B increases, the particle size of the coated abrasive also increases accordingly. By comparing Examples 2, 8 and Comparative Examples 10 and 11, it can be found that the addition of the grinding accelerator can significantly increase the grinding rate of copper under alkaline conditions. The copper removal rates of all comparative examples without the addition of the grinding accelerator are the following.

[0074] Table 5 Components and evaluation results of the grinding compositions of Examples 2, 6-12 and Comparative Example 9

[0075]

[0076]

[0077] By comparing Examples 2, 6-12, it can be found that when the molecular weight of the second polymer B is greater than the molecular weight of the first polymer A, and the molecular weight of the second polymer B is not too large, the stability time of the grinding composition is longer, and the grinding composition has a higher copper removal rate. When the molecular weight of the second polymer B is less than or equal to the molecular weight of the first polymer A, the stability time of the grinding composition is longer, but the copper removal rate of the grinding composition is relatively low. From the viewpoint of grinding materials at a higher grinding speed and extending the abrasive agglomeration sedimentation time, the coated aluminum oxide abrasive particle size range is preferably between 120-180nm. Examples 2 and 8 are the most preferred embodiments, and the grinding composition can be stored for a long time and has a high grinding efficiency.

[0078] Comparative Example 9 shows that too high a molecular weight of the second polymer B will also result in a too thick coating layer, which will cause the aluminum oxide abrasive particles to agglomerate, reduce stability, and reduce the grinding efficiency. In addition, the overall viscosity of the grinding composition is too high, which is not conducive to dispersion.

[0079] Table 6 Components and evaluation results of polishing compositions of Examples 2, 6-9, 13-17

[0080]

[0081] By comparing Examples 6-7 and Examples 13-14, it can be found that when the molecular weight of the second polymer B is less than or equal to the molecular weight of the first polymer A, the feeding order of the first polymer A and the second polymer B has no effect on the particle size of the aluminum oxide abrasive after coating, and the grinding efficiency of the final grinding composition is slightly different.

[0082] By comparing Examples 2, 8-9, and 15-17, it can be found that when the molecular weight of the second polymer B is greater than the molecular weight of the first polymer A, the order of adding the first polymer A and the second polymer B will affect the coating of the aluminum oxide abrasive. In Examples 15-17, the first polymer A and the second polymer B are added at the same time. Compared with first adding the first polymer A and then adding the second polymer B, the copper removal rate of the grinding composition is greatly reduced, the stability of the aluminum oxide abrasive is reduced, and the storage time of the grinding composition is shorter. By comparing Examples 2 and 8-9, it can be seen that if the first polymer A is added first and then the second polymer B is added, the agglomeration rate of the abrasive will not be increased, the grinding composition can be stored for a long time, and its copper removal rate is high.

[0083] Although the implementation scheme of the present application has been disclosed as above, it is not limited to the applications listed in the specification and implementation scheme. It can be fully applicable to various fields suitable for the present application. For those familiar with the art, additional modifications can be easily implemented. Therefore, without departing from the general concept defined by the claims and the scope of equivalents, the present application is not limited to the specific details and the implementation schemes shown and described herein.

Claims

1. A polishing composition, characterized in that include: Alumina abrasive particles with an average primary particle size of 80-140 nm, a first polymer, a second polymer, a grinding accelerator, and a pH adjuster, wherein the first polymer and the second polymer will ionize hydrogen ions and negatively charged groups in an aqueous solution, the molecular weight of the second polymer is in the range of 2000-100000 g / mol, and the pH value of the grinding composition is 8-10; The polishing composition comprises the following preparation method: S1: adding the first polymer to water, then adjusting the pH to 4-6 with the pH adjuster, adding the dispersion of the aluminum oxide abrasive under high-speed shearing, and dispersing for 2 hours; S2: adding the grinding accelerator and adjusting the pH to 8-10 with the pH regulator; Wherein, the second polymer is added in the step S1.

2. The polishing composition according to claim 1, wherein The second polymer has a carboxyl group and / or a phosphoric acid group.

3. The polishing composition according to claim 2, wherein The second polymer is selected from one or more of polyacrylic acid, phosphino-polyacrylic acid, and polystyrene sulfonic acid.

4. The polishing composition according to any one of claims 1 to 3, characterized in that The molecular weight of the second polymer is greater than the molecular weight of the first polymer.

5. The polishing composition according to any one of claims 1 to 3, characterized in that The second polymer is added after the dispersion of the aluminum oxide abrasive grains.

6. The polishing composition according to any one of claims 1 to 3, characterized in that The molecular weight of the first polymer is in the range of 2000-40000 g / mol.

7. The polishing composition according to claim 6, wherein The first polymer is a sulfonic acid polymer, and the first polymer is selected from one or more of poly(2-acrylamido-2-methyl-1-propanesulfonic acid), poly(3-acrylamido-1-propanesulfonic acid), and polyacrylamide-polypropylenesulfonic acid copolymer.

8. The polishing composition according to any one of claims 1 to 3, characterized in that The content of the first polymer is in the range of 0.1-1.2 wt %, and the content of the second polymer is in the range of 0.02-0.2 wt %.

9. The polishing composition according to any one of claims 1 to 3, characterized in that The grinding accelerator is a small molecule acid selected from one or more of glycine, citric acid, malonic acid and tartaric acid.

10. A method for chemical mechanical polishing of a substrate, characterized in that: include: (i) contacting a substrate with a polishing pad and the polishing composition according to any one of claims 1 to 9, (ii) moving the polishing pad relative to the substrate with the polishing composition between the polishing pad and the substrate, and (iii) grinding away at least a portion of the substrate to abrade the substrate.

Citation Information

Cited By

  • Slurry combined liquid and electronic device

    CN121108882A

  • A slurry composition and electronic device

    CN121108882B